2011
DOI: 10.1111/j.1471-0528.2011.02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing clean intermittent catheterisation and transurethral indwelling catheterisation for incomplete voiding after vaginal prolapse surgery: a multicentre randomised trial

Abstract: Objective To compare clean intermittent catheterisation with transurethral indwelling catheterisation for the treatment of abnormal post-void residual bladder volume (PVR) following vaginal prolapse surgery.Design Multicentre randomised controlled trial.Setting Five teaching hospitals and one non-teaching hospital in the Netherlands.Population All patients older than 18 years experiencing abnormal PVR following vaginal prolapse surgery, with or without the use of mesh. Exclusion criteria were: any neurological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 24 publications
0
46
1
Order By: Relevance
“…The organism found most is E. coli followed by Enterococcus sp and Klebsiella pneumoniae . Hakvoort et al [15] demonstrated that patients with transurethral catheters greater than 72 hours were more likely to develop a UTI postoperative after vaginal surgery. Indwelling Foley catheter use may play a role in non- E. coli cultures and may provide an environment that allows growth of certain microorganisms to concentrate [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…The organism found most is E. coli followed by Enterococcus sp and Klebsiella pneumoniae . Hakvoort et al [15] demonstrated that patients with transurethral catheters greater than 72 hours were more likely to develop a UTI postoperative after vaginal surgery. Indwelling Foley catheter use may play a role in non- E. coli cultures and may provide an environment that allows growth of certain microorganisms to concentrate [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Indwelling catheters lead to increased rates of UTI compared to intermittent catheterization. In a trial of 87 women undergoing vaginal prolapse repair, patients were randomized to clean intermittent catheterization (CIC) versus indwelling catheter for the management of POUR 32. Women with CIC had significantly less risk of both bactiuria (14% versus 38%, P =0.02) and UTI (12% versus 33%, P =0.03) compared to women with an indwelling catheter.…”
Section: Managementmentioning
confidence: 99%
“…Therefore, transient retention can be expected to resolve spontaneously within 4–6 weeks with the use of some form of bladder drainage to prevent damage to the bladder. Studies have shown the use of an indwelling catheter can actually prolong catheter use by the very fact that bladder function cannot be assessed with an indwelling catheter in place 32,39. Both CIC and SPC methods allow for measurement of PVR while still maintaining bladder drainage.…”
Section: Managementmentioning
confidence: 99%
“…13 The urological literature demonstrates the superiority of ISC over indwelling catheters and many patients with neurogenic bladder prefer ISC. 2 Previous studies in patients with neurogenic bladder described improved QOL associated with ISC 6 but these benefits seemed to depend on proper patient selection, technique, support and education. 14 Patient noncompliance is associated with complications such as urinary tract infection, epididymitis and urethral trauma along with more severe complications, including bladder perforation or bladder necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 ISC is generally considered a simple, painless procedure that obviates complex surgical reconstruction and decreases the complications of indwelling catheters, such as urethral erosion, bladder stones, recurrent infection and cancer. 25 ISC has proved to be well tolerated by patients with chronic neurogenic bladder in whomsimple pharmacological or surgical solutions are not readily available. 6,7 ISC has since been popularized as a conservative means of managing neurogenic bladders, benign prostatic obstruction and bladder neck contracture.…”
mentioning
confidence: 99%